응집슬러지를 이용한 하수슬러지의 탈수성 및 침강성 개선 - 소수현; 이병하; 박준홍; 차호영; 김한수; 송경근 (대한상하수도학회, 2018)
This study aimed to investigate the feasibility of improving dewaterability and settleability of sewage sludge using coagulation sludge. When mixed with sewage sludge and coagulation sludge at 1:1 ratio, Capillary Suction Time(CST) and Specific Resistance to Filtration(SRF) decreased by about 56% and 68%, respectively. It is found that Total Solids(TS) and Volatile Solids(VS) of mixing sludge are increased by about 59% and 53%, respectively. Also, the turbidity of the mixing sludge supernatant was reduced from 99 to 16 NTU. It is observed that the mixing of sewage sludge and coagulation sludge at 1:1 showed better effect than using Poly-aluminum Chloride(PAC) coagulant at 25 mg/L.